Diallel analysis for variability in bitter gourd (Momordica charantia) - MISHRA, H N; MISHRA, R S; PARHI, G; MISHRA, S N (The Indian Journal of Agricultural Sciences, 2013)
Diallel analysis of 36 F1 hybrids of bitter gourd (Momordica charantia L.) involving 9 parents (excluding reciprocals). for 8 quantitative characters indicated frequent occurrence of dominant alleles for inheritance of the characters studied. Both additive and non-additive gene actions were involved in the character expression. Unequal distribution of genes at loci showing dominance was common in the parental population, indicating the interplay of partial dominance and dominance in character expression. Presence of dominance and complementary type of gene’ action along with low narrow-sense heritability for yield indicates that heterosis breeding would be more advantageous to get higber fruit yield in bitter gourd.